Osteoporosis and Urinary N Telopeptide - Ganesan G. Ram (Osteoporosis and Urinary N Telopeptide, 2021)
Context: Osteoporosis is a dreadful condition having a characteristic trait of lowering bone mass and decreasing the structural integrity of bone tissue . Osteoporosis fractures can occur in any part of the skeleton: most commonly occurs in forearm, thoracic, lumbar vertebrae and proximal femur. The high mortality and morbidity fracture among them is the hip fracture.The incidence of fragility hip fracture as a result of osteoporosis is on a step increase There are many ongoing research in the field of Orthopaedics, as conventional radiographs cannot accurately measure the bone loss which has led way for a non invasive investigation in measuring the bone mineral content of various parts of the skeleton. Since there are significant limitations to the current ‘gold standard’ DEXA test, considerable research is going to find a better study to replace DEXA. Any new technology must be reproducible and be able to assist in the evaluation of the quantity as well as the quality and be a good judge of someone’s risk of fracture. N- Telopeptide (NTx) has been explored as a specific and sensitive marker of bone resorption .NTx is the stable degradation end product, which could be measured both in the serum and urine. The urinary excretion is not affected by diet, and therefore shows less variation than the conventional markers. The NTx is specific to bone due to unique amino acid sequence and orientation of cross-linked alpha-2 [1] N Telopeptide. Generation of the NTx molecule is mediated by the osteoclast. Aim: To evaluate urinary n telopeptide as a diagnostic test for osteoporosis. Objective of the study is assess whether Urinary n telopeptide level can be a diagnostic test for osteoporosis. Assessing the utility of urinary n telopeptide and to study its correlation with BMD. To develop optimal cut off point for classification of osteoporosis using urinary n telopeptide values. Materials and Method: It is a prospective study done at Sri Ramachandra Institute Of Higher Education and Research (DU), Chennai. The study was carried out from August 2014 to December 2019.SRIHER (DU) ethics committee clearance was obtained before the sample collection. The inclusion criteria were female aged 65 and above, female aged 60 or less with risk factors, post-menopausal young female with one or more risk factors, male aged 70 and above, male aged less than 50 with risk factors and patients who had come within 24 hours following trivial fall fractures. The risk factors were patients having body mass index less than twenty, Asian, sedentary life style, osteoporosis or fragility fracture history in family members, sustained previous fracture or a recent fragility fracture, prolonged steroid use, more than two to three alcohol drinks per day, early menopause below forty-five years, vitamin D deficiency, depletion of testosterone hormones in male and neurological illness like dementia which makes person prone to fall. The exclusion criteria were people having any pathological fracture, chronic or acute kidney disease, liver failure, tumour and malignancy, hyperthyroidism or hyperparathyroidism and any drugs that can affect bone metabolism. The study was conducted among patients who come to Sri Ramachandra Hospital as inpatient or out patient with suspected osteoporosis. All patients were clearly explained about the study and after obtaining the consent of the patients; they were included in the study. All patients who participated in the study underwent DEXA scan, urinary N -telopeptide and biochemical tests like serum calcium, serum phosphorus, alkaline phosphatase, 25-hydroxy vitamin D and serum parathyroid. Based on the results of DEXA scan patients were divided into cases and control. Sample size was fixed as 43 in each group after consulting the statistician. Results: The mean urinary N telopeptide value in cases was 182.5 and control was 49.9 which is statistically significant .The receiver operating curve was drawn taking 1-specificity in X axis and sensitivity in Y axis . The cut off as per ROC curve was found to be 71. The sensitivity and specificity were calculated taking 71 as cut off and urinary N telopeptide test is found to have 85% sensitivity and 86% specificity . Discussion: Bone density as measured by DEXA provides a static snapshot of bones and doesn’t distinguish whether bone loss is ongoing or not. But urinary N -telopeptide is a dynamic measurement of what is actually happening in bone at any given time. The mean values of urinary N-telopeptide in the cases and the controls of the present study were 182.5 and 49.8 respectively. It was found that the significant correlations were regularly reported between bone turnover markers and BMD at the lumbar spine and total hip of the post-menopausal women. No record of sensitivity, specificity, and predictive values for BTMs in the assessment of osteoporotic patients were available. It is noted that the cut off value of urinary N- telopeptide as per receiver operating characteristic curve of the present study is 71. Taking 71 as the cut off sensitivity was calculated as 85%, specificity as 86% with an accuracy of 85.5% .Since it is a diagnostic test to reduce the false negative to minimal the cut off could be taken as 63 which would decrease the false negative further and raise the sensitivity to 92% as depicted in table 34. The normal reference value of urinary N- telopeptide in post-menopausal age group was up to 89 nmol of bone collagen equivalents/nmol creatinine. The reference value was taken from European population but no reference value was available for the Indian population. If 89 is considered as the cut off and the sensitivity is calculated it would decrease to 71 and would increase the false negative also. So arriving at a new cut off for the Indian population is mandatory and the study’s cut off of 71 for urinary N -telopeptide has good sensitivity, specificity and accuracy. From the current study 71 could be made as the cut off for diagnosing osteoporosis in order to easily delineate normal and osteopenic/osteoporotic patients. Any value more than 71 means osteoporosis/osteopenia while markedly elevated levels (>1.5-2) may indicate the co-existence of alternative bone conditions like osteomalacia. Urinary N- telopeptide assessment is cheaper than DEXA. The cost of single region DEXA scan is around 2500 rupees while urinary N- telopeptide Elisa kit is around 25000 for 100 patients. If urinary N -telopeptide test was done more frequently and more in number then the kit can be purchased in a much cheaper rate. When we use DEXA scan alone for diagnosing osteoporosis it can cause some shortcomings. Urinary N- telopeptide value is directly proportionate only to the bone resorption. The increased levels of bone resorption markers project the risk of fracture independently of the level of bone mineral density. The combination of the two diagnostic tests could be useful to improve the determination of women at high risk. Conclusion: Elevated urinary N- telopeptide can diagnose osteoporosis/osteopenia and can be a new diagnostic test in osteoporosis. Since the test is economical, less invasive and simple it can also be used as a screening test. From the current study as per receiver operating characteristics curve the cut off for classification of osteopenia/osteoporosis and normal is 71. Vitamin D value, serum PTH, serum phosphorus have no correlation with osteoporosis. For suspected osteoporosis ,it is better to go for urinary N -telopeptide and those who test positive i.e. more than 71 alone can go for current ‘gold standard’ DEXA scan. To identify the high risk of fracture the combination of these two diagnostic tests could be used. Urinary N telopeptide can very well be used both as a screening as well as a diagnostic test.